The Exploration of Psychometric Models in Teachers Performance Evaluation - Josephine Obiageli Okafor (Jurnal Indonesia Pendidikan Profesi Guru, 2025)
Background: Teacher performance evaluation plays a vital role in improving educational quality. However, achieving accuracy, fairness, and effectiveness in such evaluations remains a challenge. Psychometric models offer promising tools to enhance the validity and reliability of teacher assessments. Objective: This study aims to explore the application of psychometric models in evaluating teacher performance and to investigate how these models can improve the overall assessment process. Method: The research involves an in-depth analysis of key psychometric models, including Classical Test Theory (CTT), Item Response Theory (IRT), Generalizability Theory (GT), Structural Equation Modeling (SEM), and Multilevel Modeling (MLM). The integration of these models into teacher evaluation systems is critically examined. Result: Findings indicate that each model offers unique advantages for improving assessment accuracy and reliability. However, limitations such as potential biases, data interpretation challenges, and ethical concerns must be carefully addressed. Contextual factors such as teacher characteristics, institutional policies, and opportunities for professional development significantly affect the outcomes of psychometric-based evaluations. Conclusion: Psychometric models can strengthen teacher evaluation systems when applied thoughtfully and ethically. Their effective use requires alignment with institutional goals and attention to contextual influences. Contribution: This study contributes to the field of educational assessment by synthesizing current knowledge on psychometric models and offering insights into their practical, ethical, and policy-related implications in the context of teacher performance evaluation.